The ElectroUteroGraph: A Novel Tool for Assessing Uterine Contractions of Non-Pregnant Women - Julius Georgiou; Konstantinos Lekkas; Giorgos Varnava; Marios Sophocleous; Andreas Michaelides; Vasilios Tanos (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Uterine contractility is known to play significant role in women's health. Ultrasonography and magnetic resonance imaging have been used for assessing uterine peristalsis, however they lack practicality, objectivity, and cost-effectiveness. In this paper, the ElectroUteroGraph (EUG) and novel electrodes are introduced, to cover the unmet need of practical intrauterine contractility assessment. The EUG measures biopotentials produced by uterine muscle contraction, similar to the basis of electrocardiography. Methods: The EUG was used to fifteen healthy, non-pregnant women of reproductive age. Amplitude and frequency-related features were derived from our recordings. Results: The EUG and novel electrodes did not cause any pain or discomfort to the patients, over their multiple recording sessions. The collected data showed difference between the proliferative and luteal phase of menstrual cycle (p < 0.05). Conclusions: The EUG can accurately measure uterine electrical activity, in a simple, standardized, safe and pain-free approach, leading to objective evaluation of uterine peristalsis.